Efficacy of Antibacterial Peptides Against Peptide-Resistant MRSA Is Restored by Permeabilization of Bacteria Membranes - Ravensdale, Joshua; Wong, Zachary; O’Brien, Frances; Gregg, Keith (Frontiers in Microbiology, 2016)
Clinical application of antimicrobial peptides, as with conventional antibiotics, may be compromised by the development of bacterial resistance. This study investigated antimicrobial peptide resistance in methicillin resistant Staphylococcus aureus, including aspects related to the resilience of the resistant bacteria towards the peptides, the stability of resistance when selection pressures are removed, and whether resistance can be overcome by using the peptides with other membrane-permeabilising agents. Genotypically variant strains of S. aureus became equally resistant to the antibacterial peptides melittin and bac8c when grown in sub-lethal concentrations. Subculture of a melittin-resistant strain without melittin for 8 days lowered the minimal lethal concentration of the peptide from 170 µg ml-1 to 30 g ml-1. Growth for 24 h in 12 g ml-1 melittin restored the MLC to 100 g ml-1. Flow cytometry analysis of cationic fluorophore binding to melittin-naïve and melittin-resistant bacteria revealed that resistance coincided with decreased binding of cationic molecules, suggesting a reduction in nett negative charge on the membrane. Melittin was haemolytic at low concentrations but the truncated analogue of melittin, mel12-26, was confirmed to lack haemolytic activity. Although a previous report found that mel12-26 retained full bactericidal activity, we found it to lack significant activity when added to culture medium. However, electroporation in the presence of 50 µg ml-1 of mel12-26, killed 99.3% of the bacteria. Similarly, using a low concentration of the non-ionic detergent Triton X-100 to permeabilize bacteria to mel12-26 markedly increased its bactericidal activity. The observation that bactericidal activity of the non-membranolytic peptide mel12-26 was enhanced when the bacterial membrane was permeablised by detergents or electroporation, suggests that its principal mechanism in reducing bacterial survival may be through interaction with intracellular organelles or processes. Additionally, our results showed that the haemolytic peptide bac8c, had increased antibacterial activity at non-haemolytic concentrations when used with membrane-permeabilising surfactants.